Psychometric Properties of the Eating Disorder Inventory in Clinical and Nonclinical Populations in Taiwan. (February 2014) - Tseng, Mei-Chih Meg; Yao, Grace; Hu, Fu-Chang; Chen, Kuan-Yu; Fang, David
Objective . To examine psychometric properties and investigate factor structures of the Mandarin Chinese version of the Eating Disorder Inventory (C-EDI). Method . The Mandarin C-EDI and other self-administered questionnaires were completed by a group of female eating disorder (ED) patients ( n = 551) and a group of female nursing students ( n = 751). Internal consistency, and convergent and discriminant validities were evaluated. Exploratory and confirmatory factor analyses were conducted to examine the construct validity of the Mandarin C-EDI. Results . The Mandarin C-EDI had good internal consistency and convergent and discriminant validities. With a few exceptions, the original clinically derived eight EDI subscales were clearly identified and the factorial validity of the first-order eight-factor structure and the second-order two-factor structure showed an acceptable degree of fit to our empirical data in clinical patients. Discussion . The findings suggest that the Mandarin C-EDI is a valid tool for clinical use in Taiwan.